The Role of Constitution in Ensuring The Stability of The State System in Indonesia - Yudi, Permai (Universitas Pahlawan Tuanku Tambusai, 2025)
The constitution is the main foundation in the constitutional system that functions to regulate and direct the course of government. In Indonesia, the 1945 Constitution of the Republic of Indonesia (UUD 1945) is the constitutional footing that regulates the relationship between state institutions, the rights of citizens, and the basic principles of state administration. This article aims to analyze the role of the constitution in maintaining the stability of Indonesian governance, especially after the reformation and amendment of the 1945 Constitution. This research uses a normative qualitative approach through literature study and analysis of laws and regulations. The results of the study show that the constitution has a very central role in the constitutional system. The constitution functions as the highest legal basis that regulates the course of government and the distribution of power.Through the constitution, the balance between state institutions can be maintained so that there is no abuse of authority.In addition, the constitution guarantees the protection of the basic rights of citizens in a fair and equal manner.It becomes the main reference in resolving conflicts related to state administration.However, in its implementation, the constitution often faces various complex challenges.One of them is the difference in interpretation of articles that are multi-interpretive.The growing political dynamics also often affect the implementation of constitutional norms.Political pressure can cause deviation or manipulation of the constitution